Oralność i piśmienność praktyk szkolnych - problemy i rozpoznania - Rakoczy, Marta (Uniwersytet Wrocławski. Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych, 2015)
This article concerns linguistic practices performed in the institutions of primary education. On this basis I show that: (1) the difference between speech and writing, contrary to Ong’s argument, is not the difference between something natural and technological; (2) the difference between orality and literacy does not lie in the opposition between oral conservatism and literacy progressivism and criticism.(3); orality – as conceived by Richard Bauman’s category of performance – is an important component of literacy-oriented educational processes.
Keywords: oralność; piśmienność; edukacja wczesnoszkolna